(untitled) (Bangladesh Medical Journal, 2016)
This cross-sectional study was done to evaluate the pattern of patients suffering from pemphigus disease attending in the department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from 2006 to 2010. Thirty patients of pemphigus diagnosed clinically and confirmed by histopathology and immunology, were included in the study. Among the thirty patients, 18(60%) had pemphigus vulgaris. Among the patients of pemphigus foliaceus, 13.33% patients were in the age group of 30-45 years, among the patients of pemphigus erythematosus, 6.67% patients were in the age group of 30-45 years and among the patients of paraneoplastic pemphigus, 3.33% patients were in the age group of 46-60 years. Among the different varieties of pemphigus, highest 66.67% had the disease duration of 1 to 6 months. Male were more than female. Highest 76.50 % showed both mucosal and skin involvement as initial clinical presentation. In future, this study should be carried out on a large scale with prolong period, large sample size and in different hospitals in Bangladesh. Bangladesh Med J. 2014 Sep; 43 (3): 138-140